Are Education and Entrepreneurial Income Endogenous and Do Family Background Variables Make Sense as Instruments? A Bayesian Analysis - Jörn H. Block; Lennart F. Hoogerheide; A. Roy Thurik (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Education is a well-known driver of (entrepreneurial) income. The measurement of its influence, however, suffers from endogeneity suspicion. For instance, ability and occupational choice are mentioned as driving both the level of (entrepreneurial) income and of education. Using instrumental variables can provide a way out. However, three questions remain: whether endogeneity is really present, whether it matters and whether the selected instruments make sense. Using Bayesian methods, we find that the relationship between education and entrepreneurial income is indeed endogenous and that the impact of endogeneity on the estimated relationship between education and income is sizeable. We do so using family background variables and show that relaxing the strict validity assumption of these instruments does not lead to strongly different results. This is an important finding because family background variables are generally strongly correlated with education and are available in most datasets. Our approach is applicable beyond the field of returns to education for income. It applies wherever endogeneity suspicion arises and the three questions become relevant.
Keywords: C11; L26; M13; J24; 330; Education; income; entrepreneurship; self-employment; endogeneity; instrumental variables; Bayesian analysis; family background variables; Erfolgsfaktor; Entrepreneurship-Ansatz; Bildungsniveau; Soziale Lage; Selbstständige; Bayes-Statistik; Schätzung; Deutschland